Strategi Untuk Meningkatkan Minat Calon Mahasiswa Baru Studi Pada Fakultas Ushuluddin dan Studi Islam UIN Sumatera Utara Medan - Mhd Ali Alfateh; Sulidar Sulidar; Syukri Syukri (UIN Sumatera Utara, 2022)
The State Islamic University (UINSU) has developed rapidly in terms of development and in improving human resources. Data on the number of students from year to year fluactuates especially in the Faculty of Ushuluddin and Islamic Studies (FUSI). This research uses descriptive qualitative method with promotion mix theory, where data is obtained through two types of data sources, namely primary data and secondary data. Data collection techniques used are interviews, observations, and documentation. In this study, the data triangulation technique was used by means of source triangulation. Based on the results of the researchthat the author did, the promotional strategies used are: 1) Advertising through print and electronic media in the form of stickers, brochures, social media, and the faculty’s official website, 2) Sales promotion by offering scholarships and holding events with various prizes, 3) Personal selling is the most effective way by the Faculty because it is directly (face to face) by meeting schools inside and outside the city, 4) publicity is a way to use media to cover Faculty activities related to new student admissions, as well as media used as promotional tools, namely print media and electronic media. Factors that hinder promotional activities include lack of budget funds, lack of human resources and restrictions on activities during the covid-19 pandemic.